PEMBELAJARAN MATEMATIKA MENYENANGKAN DENGAN MEDIA PEMBELAJARAN DIGITAL - Ni Kadek Rini Purwati; Ni Luh Desi Antari (De Fermat : Jurnal Pendidikan Matematika, 2022)
Learning in the 4.0 era requires students and teachers to be able to take advantage of Information Technology (IT)-based learning media. Learning is done by utilizing digital-based learning applications that can have a fun effect on students. Learning media that are often used in digital-based learning processes usually use the Kahoot! and Quizizz platforms. The purpose of writing this article is to explain the role of educational games Kahoot! and Quizizz in supporting mathematics learning which can later be used by teachers in the classroom learning so that learning is more varied, less boring, and more fun for students. The writing of this article uses a literature study method by reviewing journals related to Kahoot! and Quizizz. The results of the study show that there are several benefits of using Kahoot! and Quizizz, namely: increasing student learning outcomes, accelerating understanding of the material, increasing students' motivation and independence, increasing thinking and learning abilities, students having a positive attitude in learning, students being more active in learning, learning is more fun and less boring and increases interest in learning.